THE RUIN OF WHITE ADVENTURERS IN MALAY ARCHIPELAGO, A STUDY TO CONRAD’S TRILOGY: ALAMYER’S FOLLY, AN OUTCAST OF THE ISLAND, AND THE RESCUE - Mugijatna Mugijatna; Sri Kusumo Habsari; Karunia Purna Kusciati, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Many English literary works were written during the colonialism era present white people as superior people. But Joseph Conrad in his trilogy, Almayer’s Folly, An Outcast of the Island, and The Rescue, present white people as defeated people. All the main characters in the novels that are white adventures are lost. Almayer, the main character in Almayer’s Folly, got bankrupt and eventually died sorrowfully; Willems, the main character in An Outcast of the Island, died at the hand of his beloved; and Lingard, the main character in The Rescue and the character in the other two novels as well, went home empty-handed. Why is the case like that? This research is a study of the trilogy in order to answer the question. Accordingly, the objective is to explain the cause of the white adventurers’ lost. This research is conducted using Ricoeur’s hermeneutics which consists of distantiation and appropriation as the methodology. The result is that, first, Almayer misunderstood the political situation and misunderstood the mind of her own daughter, Willems was in conflict with Almayer, and Lingard was unlucky; on the other hand, the leaders of the Malay people were crafty, able to make them fight to each other, and able to make a smart move. Second, the novels present objective point of views; from Malay point of views, white adventures in the Malay Archipelago caused miserable life to them but they were too strong to fight against them, while from the point of view of the white adventurers, the Malay couldn’t be trusted, cunning, and savage.